Spatial and temporal infestation rates of Apate terebrans (Coleoptera: bostrichidae) in cashew orchards in Benin, west Africa - Agboton, C.; Onzo, A.; Korie, S.; Tamo, Manuele; Vidal, S. (Entomological Society of Southern Africa, 2017)
Cashew, Anacardium occidentale L. is an important export crop in Benin, but incurs serious damage from the cashew wood borer Apate terebrans Pallas. In spite of its economic importance, the population dynamics of this beetle have never been studied, thus precluding any science-based development and implementation of control strategies. The spatial and temporal abundance pattern of A. terebrans was therefore monitored in 17 mature cashew orchards distributed across three agro-ecological zones in Benin. In each orchard, 30 cashew trees were chosen at random and inspected monthly for two consecutive years. As this insect feeds inside branches and trunks by boring holes, direct observations of adults inside the tree are not possible. Therefore infestations of trees were estimated by the occurrence and number of fresh entry holes. Over the two-year observation period, infestations in the cashew trees by A. terebrans started in September, peaked in January–February and sharply declined thereafter, reaching zero by July–August. Whereas the infestation rates were statistically similar between sampling years or among agro-ecological zones, they differed significantly among sampling months. Aggregation indices calculated using Taylor's power law indicated that A. terebrans has an aggregated spatial distribution. Values of the Spatial Analysis by Distance IndicEs (SADIE) index indicated that the spatial pattern of the infestation in a given year does not depend on the pattern observed in the previous years, suggesting that A. terebrans generally prefers to infest new trees. Implications of our findings for the development, implementation and monitoring of effective control strategies against A. terebrans are discussed.